Pond's Brand Community Potentials Among High School Female Students in Bandung - Nasution, Reza Ashari; Radiatni, Kaninia (SBM ITB, 2009)
Community based marketing becomes an effective approach that can give significant benefits for the practicing company. Accordingly, analysis on brand community potential for a particular brand becomes a very interesting topic to be researched. In this project, a study on female high-school-students was done to analyze that opportunity of Pond’s brand to build brand community among this target market in Bandung. The finding shows that the chance for Pond’s to develop brand community in Bandung is high. Most respondent embrace similar value with regards to beauty and socialization. Most of them also want to join the brand community. They also give very positive answer about the overall perception about Pond’s that indicates that they have positive attitude toward the product. However, there are significant number who refuse to be a member of Pond’s brand community. Cross-tabulation analysis is conducted to determine significant factor that differentiative between the two groups of students. Keywords: Pond’s, brand community, beauty, value, bandung